Peningkatan Keamanan Pengiriman Pesan Teks: Kombinasi Advanced Encryption Standard (AES) 128 dan Least Significant Bit (LSB) - Yulia Fatma; Afdhil Hafid; Heru Oktavian Dani (JUSIFO : Jurnal Sistem Informasi, 2020)
Confidentiality in transfer the messages is an important thing to maintain. Increased security in transfer the messages can be improved using cryptography and steganography. This article aims to apply a combination of AES 128 cryptography and LSB steganography in an application, and measures the quality of the stego-image. In this article, the AES 128 algorithm is used for the encryption process of secret messages and the LSB algorithm for the process of inserting secret messages in the cover image. PSNR is used to measure the quality of the stego-image, by comparing the cover image and the stego-image. This research produces an application that can be used for the security of sending text messages by combining the AES 128 algorithm in the plaintext encryption and the LSB algorithm in the secret message insertion process. In term of measuring the quality of the stego-image, it was found that the character length of the secret message would have an impact on the MSE and PSNR values. This means, the longer the character of the secret message will affect the quality of the stego-image.